The Middle East and Globalization - Stetter, Stephan. author. aut Link
X, 274 p. 1 illus.
Keywords: The Middle East and Globalization discusses past and contemporary political, societal, economic, and cultural trends in the Middle East against the background of comprehensive theories of globalization. The chapters draw on a shared methodological approach, looking at the fractures and horizons of globalization that are shaping the Middle East.